Anticancer Activity of New Copper (II) Complexes with 6-Thiguanine Drug - Singh, Birjesh; Mishra, Jyotsna; Pitre, K.S.; Pradhan, Alka; Soni, Puspender (International Journal of Biotechnology for Wellness Industries, 2013)
A new complex has been synthesized of Cu (II) complex with 6-thioguanine and phyico-chemical characterized by amperometry, polarography elemental analysis and FTIR spectroscopy. After Synthesis of metal complex, it was evaluated it for antibacterial and antifungal activities against various pathogenic microorganisms such as; Streptococcus aureus, Proteus. M., klebsiella pneumonia and Asperginus niger, Nigrosporan S.P. B16-F10 melanoma cell and C-57BL/6 mice has been used for anticancer screening of metal complex for in vitro and in vivo study. The result of pharmacological studies with M: L revealed that the complex is more potent as compared to the pure drug as regards to its anticancer activity.